From complexity to clarity: A climate security vulnerability measure for policymaking - Liebig, Theresa Ines; Guerrero, Omar; Guariso, Daniele; Craparo, Alessandro Carmelo William; Basel, Ashleigh; Taiwo, Ibukun (2023)
The CGIAR Focus Climate Security and The Alan Turing Institute’s Computational Social Science Group's collaboration addresses the need for a reliable and efficient approach to decision-making and policy development by developing an innovative analytical framework to construct a systemic measure that analyzes structural features among key components of the climate security nexus, to support contextualized and climate security-sensitive decisions for policies, programs, or finance.